2008
DOI: 10.2147/btt.s3356
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic options in the management of acromegaly: focus on lanreotide Autogel®

Abstract: BackgroundIn acromegaly, expert surgery is curative in only about 60% of patients. Postoperative radiation therapy is associated with a high incidence of hypopituitarism and its effect on growth hormone (GH) production is slow, so that adjuvant medical treatment becomes of importance in the management of many patients.ObjectiveTo delineate the role of lanreotide in the treatment of acromegaly.MethodsSearch of Medline, Embase, and Web of Science databases for clinical studies of lanreotide in acromegaly.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 210 publications
(196 reference statements)
0
15
0
Order By: Relevance
“…Indeed, some authors reported safe GH levels in 48-64% of patients and normal IGF-1 levels in 47-61%, while others showed a higher percentage of biochemical control (38-80% for GH and 39-80% for IGF-1). [30][31][32][33] Concerning the effect on tumor mass, a significant shrinkage (>20-25% volume reduction) was observed in about 63% of patients treated with LAN Autogel and 66% of those treated with OCT LAR. 34,35 Therefore, the efficacy of OCT LAR and LAN Autogel is considered superimposable.…”
Section: First-line Medical Treatment and Biochemical Controlmentioning
confidence: 98%
“…Indeed, some authors reported safe GH levels in 48-64% of patients and normal IGF-1 levels in 47-61%, while others showed a higher percentage of biochemical control (38-80% for GH and 39-80% for IGF-1). [30][31][32][33] Concerning the effect on tumor mass, a significant shrinkage (>20-25% volume reduction) was observed in about 63% of patients treated with LAN Autogel and 66% of those treated with OCT LAR. 34,35 Therefore, the efficacy of OCT LAR and LAN Autogel is considered superimposable.…”
Section: First-line Medical Treatment and Biochemical Controlmentioning
confidence: 98%
“…The disease is related to the excessive production of growth hormone after the fusion of epiphyseal plate. [5] Acromegaly is a rare disease, with a prevalence of 40 to 70 cases per million inhabitants and an annual incidence of 3 to 4 new cases per million inhabitants without geographical or sex differences. [5,6] However, a recent study performed in Belgium suggests it to be around 100-130 cases per million inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Acromegaly is a rare disease, with a prevalence of 40 to 70 cases per million inhabitants and an annual incidence of 3 to 4 new cases per million inhabitants without geographical or sex differences. [5,6] However, a recent study performed in Belgium suggests it to be around 100-130 cases per million inhabitants. Owing to its insidious onset, acromegaly is often diagnosed late (4 to more than 10 years after onset, average -40 years) as seen in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GH < 2.5 µg/l and a normalized IGF-1), demonstrating that both formulations have equal efficacy [22,28,38]. Nevertheless, Somatuline ® autogel ® is typically preferred by patients over Sandostatin ® LAR owing to its more convenient regime of administration: it is self-or care-giver injected and, unlike Sandostatin ® LAR, does not require a medically-qualified person for administration [39].…”
Section: Formulations Of Somatostatin Analoguesmentioning
confidence: 99%